Exploring the electronic band structure, spectroscopic signatures, and structural properties of Er3+-based hydroxyapatites co-doped with Ce3+ions - Ahmed, Lana Omar; Bulut, Niyazi; Banares, Luis; Kaygili, Omer; Kebiroglu, Hanifi; Ates, Tankut; Ates, Burhan (Elsevier, 2023)
In this work, we have investigated Ce3+ and Er3+ co-doped hydroxyapatite (HAp) structures both theoretically and experimentally for the first time. The Ce3+ content was incrementally varied in steps of 0.13 at. %, ranging from 0.13 at. % to 0.78 at. %. Meanwhile, the Er3+ content remained constant at 0.39 at. % for all samples. We employed X-ray diffraction, Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy, thermogravimetric analysis, differential thermal analysis, differential scanning calorimetry, and in vitro biocompatibility tests to examine the prepared samples. Our findings demonstrate that the thermal behavior, morphology, and other crystal structure-related parameters are significantly influenced by the con-centration of Ce3+. The formation of HAp structures was confirmed through FTIR and Raman spectroscopic analyses. Furthermore, we conducted theoretical calculations to determine the linear absorption coefficient, density of states, and bandgap. These calculations revealed that the addition of Ce3+ atoms at varying concen-trations resulted in an increase in density from 3.174 to 3.195 g cm-3, while the bandgap gradually decreased from 4.16 to 4.10 eV, except for the 0.26Ce-0.39Er-HAp and 0.52Ce-0.39Er-HAp compositions, where the energy bandgap exhibited an increase.
Keywords: Bandgap; X-ray diffraction; Spectroscopic study; Hydroxyapatite